IDENTIFIKASI FAKTOR EKSTERNAL DAN FAKTOR INTERNAL LINE BANK - Raisha Azzura Razak (2023)
Knowing the external and internal factors of Line Bank service features. SWOT analysis is used in business management to evaluate the strengths, weaknesses, opportunities and threats of an organization or project. Collecting data using literature study sources is often referred to as a library research method or library research. Line banks have quite good opportunities because they can open banking products quickly, but there are still threats that need to be faced like other digital banks. Line bank also has many advantages and disadvantages of banking products that must be continuously improved in order to retain customers. Line Bank needs to continue to innovate and improve products and services..